RECONSTRUCTION OF PRISONERS DEVELOPMENT SYSTEM INTO CORRECTIONAL SYSTEM - Nurul Listiyani (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2015)
Legal issues in this paper is about prisoners development originally oriented to prisoners development system that amanded into correctional system by Keputusan Menteri kehakiman Republik Indonesia Nomor M.02-PK.04.10 tahun 1990. Using normative law sociological research methods analyzerd that Correctional Institute of banjarmasin, South of Borneo, oriented to the new system of prisoners development although not all of it can be adopted in practice. The small number of correctional officers which is inversely proportional to over capacitu condition of prisoners become the main detention factor in achiieving the development patterns of prisoners and detainess based on correctional system prisoners, correctional officers, and society is the component of it which have their own role basically in pracice. Keywords : Prisoners, Correctional Institute, Correctional System.